Palliative treatment of malignant intestinal obstruction with EUS-guided ileosigmoidostomy – a case report - Zundler, Sebastian; Wolff, Kerstin; Leppkes, Moritz; Gaza, Anne; Haberkamp, Sophie; Strobel, Deike; Siebler, Jürgen; Neurath, Markus; Waldner, Maximilian (Zeitschrift für Gastroenterologie, 2024)
We present the case of a 70-year-old patient of Caucasian origin under palliative chemotherapy for metastasized colorectal cancer, who presented with signs of complete small bowel obstruction six months after placement of a diverting ileostomy. Following previous tumor perforation, he was not considered a candidate for further surgical intervention. Thus, endoscopic ultrasound-guided enterocolostomy (i.e., ileosigmoidostomy) with a lumen-apposing metal stent was successfully performed in a coloenteric approach to restore the passage. Oral nutrition could be resumed the next day, and the patient could be discharged in substantially improved condition after three days.
CRIS-Team Scopus Importer:2024-12-13
Keywords: endoscopic ultrasound; endoscopy; oncology